Reversible inhibition of central precocious puberty with a long acting GnRH analogue. Issue 9 (September 1985) - Ward, P S; Ward, I; McNinch, A W; Savage, D C
Abstract : A 7 year old girl with precocious puberty was treated with buserelin, a long acting analogue of gonadotrophin releasing hormone. Spontaneous and stimulated gonadotrophin secretion became prepubertal but returned to pubertal values when buserelin was withdrawn, suggesting that normal sexual maturation should follow cessation of treatment.